A Proteção do meio ambiente como dever fundamental - Brasil, Paula Emília Moura Aragão de Sousa (2016)
This thesis has as its object the analysis of the environmental legal protection, as a individual legal duty. As a fundamental duty in Brazilian law. For the development of the thesis some introductory topics are described such as the possible reasons and outlines of an environmental crisis and its approach by branches of non juridical sciences. The study also concerns the environmental ethics and its variations. Then, the environmental crisis is inserted in the Law context, seeking support environmental protection in juridical principles, international documents and constitutions, including the Brazilian one. Next, the text analyzes the duties, since its moral sense until the legal one. A brief theory of the fundamental duties is drawn to justify the existence of a fundamental duty of environmental protection in Brazilian Law. It approaches, then, the legal system of this fundamental duty of protection of the environmental in the Brazilian legal system, highlighting aspects such as the object of the environmental legal guardianship, the recipients of the legal standart of environmental protection duty, as some very important environmental law principles as the access to environmental goods egalitarian, the social function of property, prevention and precautionary principle, polluter pays principle, information and environmental education and sustainable development.